Critical Degree of COVID-19 Pneumonia in A Man with HIV - Ukaga, Tenno; Ansori, Isa (Devotion : Journal of Research and Community Service, 2023)
Severe acute respiratory syndrome corona virus-2 (SARS-CoV-2), appeared in the city of Wuhan, China. SARS-CoV-2 causes the Coronavirus disease 2019 (COVID-19), which has resulted in the most devastating pandemic in modern world history. Epidemiological data show that COVID-19 infection with a poor prognosis occurs in the general population with chronic systemic immune deficiency and inflammatory conditions in patients. People with HIV/AIDS (ODHA) have a higher risk of being infected with COVID-19. Research related to COVID-19 infection in HIV/AIDS patients still yields different results in terms of susceptibility to infection, clinical characteristics, severity of symptoms, and prognosis. It is aimed that this case will provide an up-to-date picture of the incidence of COVID-19 in HIV cases The method used in this study is qualitative and a case study of shortness of breath patients. Clinical characteristics of COVID-19 patients and age range 26-82 years. In hospitalized patients, the appropriate treatment strategy depends on the severity of the disease. Treatment for COVID-19 patients with HIV co-infection is the same as for COVID-19 without HIV infection. Immunosuppression in COVID-19 can delay viral clearance and prolong the course of the disease. Monitoring viral load and CD4 count are variables that influence the severity of symptoms. Critical degree Covid 19 patients with HIV have a poor prognosis, but with adequate management the patient experiences clinical improvement and can go home for independent isolation.